Endometrioid adenofibroma of ovary: A case report and review of literature. Issue 8 (22nd February 2023) - Tong, Hai-Chao; Li, Ying-Chun; Li, Le-Yao; Xu, Hong-Tao; Ma, Shuang; Zhang, Wan-Lin; Wildes, Tyler; Yang, Lian-He; Wang, Endi
Abstract : Rationale: Endometrioid adenofibroma is a benign epithelial neoplasm of the ovary, most of which are often unilateral. The symptoms of endometrioid adenofibroma are often nonspecific and misleading. Therefore, a full understanding of the characteristics, diagnosis, and treatment methods of this disease is of great importance. In this study, we report a 34-year-old woman who was found with an unidentified mass on the right ovary during the physical examination 3 years ago with nosymptoms or signs. Patient concerns: A 34-year-old Chinese female was found with an unidentified 6 cm mass on the right ovary for 3 years that presented with no symptoms or signs. Diagnosis: Pelvic ultrasound revealed a 6 cm cystic solid mixed mass on the right ovary. Through histological and immunohistochemical examinations, the tumor mass was finally diagnosed as endometrioid adenofibroma of ovary. Interventions: To confirm the diagnosis, the ovarian tumor was laparoscopically resected. Outcomes: The patient returned to hospital after 3 months with no recurrence or postoperative complications. Lessons: Endometrioid adenofibroma is a benign epithelial neoplasm of the ovary. Complete surgical resection is required and rare cases can recur. Postsurgical pathologic and immunohistochemical testing can confirm a diagnosis of endometrioid adenofibroma. It is important to understand of the key points of differential diagnosis of the disease due to the different prognosis and clinical treatment.